A proposal for an individualized pharmacogenetic-guided isoniazid dosage regimen for patients with tuberculosis - Jung JA; Kim TE; Lee H; Jeong BH; Park HY; Jeon K; Kwon OJ; Ko JW; Choi R; Woo HI; Koh WJ; Lee SY (Dove Medical Press, 2015)
Jin Ah Jung,1 Tae-Eun Kim,2 Hyun Lee,3 Byeong-Ho Jeong,3 Hye Yun Park,3 Kyeongman Jeon,3 O Jung Kwon,3 Jae-Wook Ko,4 Rihwa Choi,5 Hye-In Woo,6 Won-Jung Koh,3 Soo-Youn Lee4,5 1Department of Clinical Pharmacology, Inje University College of Medicine, Inje University Busan Paik Hospital, Busan, Korea; 2Department of Clinical Pharmacology, Konkuk University Medical Center, 3Division of Pulmonary and Critical Care Medicine, Department of Medicine, 4Department of Clinical Pharmacology and Therapeutics, 5Department of Laboratory Medicine and Genetics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea; 6Department of Laboratory Medicine, Samsung Changwon Hospital, Sungkyunkwan University School of Medicine, Changwon, Korea Background/aim: Isoniazid (INH) is an essential component of first-line anti-tuberculosis (TB) treatment. However, treatment with INH is complicated by polymorphisms in the expression of the enzyme system primarily responsible for its elimination, N-acetyltransferase 2 (NAT2), and its associated hepatotoxicity. The objective of this study was to develop an individualized INH dosing regimen using a pharmacogenetic-driven model and to apply this regimen in a pilot study.Methods: A total of 206 patients with TB who received anti-TB treatment were included in this prospective study. The 2-hour post-dose concentrations of INH were obtained, and their NAT2 genotype was determined using polymerase chain reaction and sequencing. A multivariate regression analysis that included the variables of age, sex, body weight, and NAT2 genotype was performed to determine the best model for estimating the INH dose that achieves a concentration of 3.0–6.0 mg/L. This dosing algorithm was then used for newly enrolled 53 patients.Results: Serum concentrations of INH were significantly lower in the rapid-acetylators than in the slow-acetylators (2.55 mg/L vs 6.78 mg/L, median, P<0.001). A multivariate stepwise linear regression analysis revealed that NAT2 and body weight independently affected INH concentrations: INH concentration (mg/L) =13.821-0.1× (body weight, kg) -2.273× (number of high activity alleles of NAT2; 0, 1, 2). In 53 newly enrolled patients, the frequency at which they were within the therapeutic range of 3.0–6.0 mg/L was higher in the model-based treatment group compared to the standard treatment group (80.8% vs 59.3%).Conclusion: The use of individualized pharmacogenetic-guided INH dosage regimens that incorporate NAT2 genotype and body weight may help to ensure achievement of therapeutic concentrations of INH in the TB patients. Keywords: tuberculosis, pharmacogenomics, NAT2 genotype, INH regimen